Books business : publishing past present and future - Epstein, Jason (New York : W. W. Norton & Co., 2001)
"Jason Epstein has led arguably the most creative career in book publishing during the past half-century. In 1952, while a young editor at Doubleday, he created Anchor Books, which launched the so-called quality paperback revolution and established the trade paperback format. In the following decade he became co-founder of The New York Review of Books. In the 1980s he created the Library of America, the prestigious publisher of American classics, and The Reader's Catalog, the precursor of online bookselling."
"In this short book he discusses the severe crisis facing the book business today - a crisis that affects writers and readers as well as publishers - and looks ahead to the radically transformed industry that will revolutionize the idea of the book as profoundly as the introduction of movable type did five centuries ago."--Jacket
t Groves of Academe Modern Time
Includes index
Keywords: Publishers and publishing -- History -- 20th century; Publishers and publishing -- Forecasting